Karanikola, Maria - (:unkn) unknown (My University, 2026)
Dr Maria Karanikola is Associate Professor at Cyprus University of Technology since 2008. She holds a BSc in Nursing (1999) from the National and Kapodistrian University of Athens, School of Nursing, as well as a Master’s degree in Mental Health (2001) and a PhD in Mental Health Nursing (2006) from this institute. She has a clinical experience as a staff nurse in a variety of clinical settings, including mental health services. Her main research interest focuses on the interaction between the healthcare milieu and the mental/psychological well-being of clinicians and patients, with special interest in mental health, emergency, critical care and oncology settings. Moreover, she is exploring the experience of mental disease and of receiving/delivering care, and how this may affect patients’ and providers’ neuro-cognitive and psychological responses, their meaning-making and values. Additionally, she has explored professional role issues among nurses and their association with mental/psychological well-being parameters, as well as with the quality and safety of delivered care. In the immediate future she intends to explore the effectiveness of psychological support/educational interventions in nurses’ and patients’ mental/psychological status, as well as the role of neuro-cognitive functioning in clinicians’ and patients’ response to clinical issues.
Keywords: Mental Health, Occupational Health, Qualitative Methodology, Bioethics, Education, Vulnerable Populations; nursing